Socialization Of Waste To Energy Transformation: Innovation And Future Opportunities In Penang Island - I G. Ayu Arwati; Nurato Nurato; Dafit Feriyanto; Imam Hidayat; Muhammad Fitri; Hadi Pranoto; Sagir Alva; Dianta Ginting; Nanang Ruhyat; Alvian Noviyanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Effective waste management is a major challenge in the modern era, especially with the increasing volume of waste produced by society. Transforming waste into energy offers an innovative solution that not only reduces environmental impact but also opens up economic and social opportunities. Through technologies such as biogas, incineration, pyrolysis, and gasification, waste can be converted into sustainable renewable energy sources. This socialization aims to increase public and stakeholder awareness of the importance of innovative waste management and its benefits for the environment and future economy.By understanding the technology, opportunities, and challenges that exist, it is hoped that the community and government can play an active role in supporting the mission towards more environmentally friendly waste management and reducing carbon emissions.